THE ECONOMIC EFFECT OF CORRUPTION: A THEORETICAL ASPECT - Merezhko , S. I. (Theory and Practice of Public Administration, 2021)
Against the background of the widespread perception of corruption as a negative phenomenon, moreover, as a crime that is directly or indirectly enshrined in the legal field of modern states, it is necessary to recognize the existence of lack unity and some controversy in that question by economists and other researchers and even the existence of positive impact on economic development. Some researchers believe that corruption can increase efficiency because it removes government-imposed rigidities that hinder investment and hinder other growth-friendly economic decisions. However, above theoretical arguments, which positively assess corruption, do not stand up to criticism. First, restrictions and rules are not exogenous and immovable features of society; society is not born with these harsh traits. They are created, and in fact can be intentionally created by officials to receive bribes. Second, those who can give the highest bribes are not the most cost-effective, but rather the most successful in finding rent. If bribes are considered investments, then those who pay it should consider these bribes as high-return investments. The fight against corruption cannot be separated from state reform. It is important to note that corruption will be reduced only in countries where governments want to reduce their functions. In any case, an effective strategy aimed at reducing corruption requires political strength to implement it and be active in the following areas: 1. Formation in the leadership of the state and the state authorities of zero tolerance for corruption. 2. Policy changes that reduce the demand for corruption, through the reduction of regulations and policies such as tax incentives, as well as by maintaining the most transparent and non-discriminatory measures. 3. Reducing the supply of corruption by increasing wages in the public sector, increasing incentives for honest behavior, introducing a system of control and mulcts for public servants. 4. Resolve the issue of financing political parties. Communities can do much to reduce the intensity of corruption, but none of this will lead to its complete eradication. The necessary measures may require major changes in the implementation of all public policy.